GeNETICS of some polyGENIC traits in hexaploid bread wheat in high temperature stress - M. Irshad; I. Khaliq; J. Iqbal; N. Hussain; M. Aslam; K. Hussain; N. Din (Journal of Animal and Plant Sciences, 2014)
A study was conducted to investigate the inheritance pathway of some physio-morphological traits of wheat in the Department of Plant Breeding and Genetics, University of Agriculture, Faisalabad, Pakistan from 2008-09 to 2010-11.Two hundred and twenty genotypes of spring wheat of diverse origin were preliminary screened in heat stress and stress free conditions during 2008-09 and out of these four high temperature stress tolerant and three thermolabile parental genotypes were selected. Forty two F1progeniesof 7×7 diallel crosses alongwith parents were evaluated in stress free and heat stress environments during 2010-11.F1 hybrids Bhakkar-02×SH-02 and its reciprocal had the highest grain yield per plant (28.00 and 27.33g) with a reduction of 29.42% and 26.78%, in heat stress respectively. The results revealed significant genotypic differences (P< 0.01) for all parameters. Adequacy tests indicated that data for spike length, grains per spike, 1000-grain weight and grain yield per plant were fit for additive dominance model, while those of dry biomass per plant at maturity were partially adequate. Additive component of variation (D) was significant (P< 0.01) and prominent over H1 and H2 components for days to anthesis, grains per spike, 1000-grain weight, grain yield per plant and dry biomass per plant at maturity while dominant genes were mainly controlling factors for spike length and was confidently sustained by the value of H1/D0.5. Values of h^2 andH2/4H1 demonstrated asymmetrical and unequal distribution of dominant genes in parents for most of the characters. Spike length, dry biomass per plant at maturity, grains per spike, 1000-grain weight and grain yield per plant exhibited high narrow sense heritability due to the existence of additive gene action with partial dominance suggesting that these traits might be useful for the development of high temperature stress tolerant varieties by modified pedigree selection method.
Keywords: Spring wheat; terminal heat stress; physio-morphological traits; heritability; additive; asymmetrical; genetics; diallel